Child Stunting in Papua, Indonesia: Determinants and Pathways from a UNICEF Framework–Guided Narrative Review - Ahmar, Hamdiah; Yulidia, Herlina; Andriany, Alia; Pesurnay, Yanti; Sianturi, Sintong Halomoan; Lilis, Lilis (Journal of Current Health Sciences, 2026)
Stunting remains a major public health problem in Papua, Indonesia, with burdens concentrated in remote and rural communities. This narrative review synthesized evidence on determinants of stunting among children under five and organized findings using the UNICEF framework (immediate, underlying, and basic/enabling causes). A structured Google Scholar search (2015–2025) identified 39 records; after deduplication and screening, 11 studies were included for thematic narrative synthesis. Across included studies, infection pathways—especially maternal malaria and early-life malaria exposure—were consistently associated with stunting. Case-control evidence also linked adverse birth outcomes (low birth weight and short birth length) to higher odds of later stunting. Nutrition-related determinants included inadequate diet quality, micronutrient gaps (iron and iodine), and maladaptive caregiver feeding practices during complementary feeding, while breastfeeding indicators showed mixed associations across settings. Environmental constraints, notably poor sanitation and limited access to safe water, repeatedly co-occurred with structural disadvantages such as low maternal education, poverty, rural residence, and restricted access to primary health services. The evidence supports integrated, Papua-specific action: combine malaria prevention and treatment in pregnancy with the first-1,000-days nutrition agenda, strengthen WASH infrastructure, expand routine growth monitoring and counseling, and deliver family-centered support for feeding and timely care-seeking. Abstrak: Stunting masih menjadi masalah kesehatan utama di Papua, Indonesia, terutama di wilayah terpencil dan perdesaan. Tinjauan naratif ini mensintesis bukti determinan stunting pada anak di bawah lima tahun dan menata temuan dengan kerangka UNICEF (segera, mendasar, dasar/pemungkin). Pencarian terstruktur di Google Scholar (2015–2025) menemukan 39 rekaman; setelah deduplikasi dan seleksi, 11 studi diinklusi dan dianalisis secara naratif tematik. Jalur infeksi—khususnya malaria pada kehamilan dan paparan malaria awal kehidupan—secara konsisten berasosiasi dengan stunting. Bukti kasus-kontrol juga menunjukkan luaran kelahiran buruk (BBLR dan panjang lahir pendek) berkaitan dengan odds stunting lebih tinggi. Jalur gizi meliputi kualitas diet rendah, defisit mikronutrien (zat besi, yodium), serta praktik pemberian makan pengasuh yang kurang tepat pada periode MP-ASI; indikator menyusui menunjukkan hasil yang bervariasi antar lokasi. Kendala lingkungan (sanitasi buruk, air minum tidak aman) sering muncul bersama kerentanan struktural seperti pendidikan ibu rendah, kemiskinan, tinggal di perdesaan, dan akses layanan primer terbatas. Temuan mendukung aksi terpadu spesifik Papua: integrasikan layanan malaria maternal dengan agenda gizi 1.000 HPK, perkuat WASH, perluas pemantauan pertumbuhan rutin dan konseling, serta dukungan keluarga untuk pemberian makan dan pencarian layanan tepat waktu, terutama di daerah endemis malaria dan distrik dengan hambatan geografis tinggi secara berkelanjutan.